Economics as a Discipline of Instrumental Reason. Looking at Economics as a Science from the Perspective of the Frankfurt School of Philosophy - Komusińska, Jagoda (Annales. Etyka w Życiu Gospodarczym, 2015)
The article is built around the analysis of The critique of instrumental reason by Horkheimer, applied to issues connected with the philosophy of economics. Positive economics is under-stood as an example of a discipline where the pragmatic paradigm has been implemented. Therefore, economics functions within the boundaries of what Horkheimer called instrumental rationality. The starting point is the intellectual source shared by economics and the Frankfurt School, namely Kant’s philosophy of rationality. In the first part of the article, three of Kant’s ideas that are fundamental to economics are presented, and then the development of their application in philosophy of science, as seen by Horkheimer in 1947, is laid out. The second part of the article consists of enumerating various distinctive features of economics that set it apart from other social sciences and which constitute factors for which it can be considered a realm of the reign of ‘instrumental rationality’, with all the threats such an approach provokes. The above-mentioned features concentrate on treating humans in economics as a means, not as a goal. This aspect of the philosophy of science of the Frankfurt School (unlike its critique of capitalism as an economic system) has not been widely received.